USE OF GROUNDWATER IN SELECTED AREAS (AL-RASHIDIYA AND SOUTHERN REGION'S BAGHDAD) OF EASTERN BAGHDAD OIL FIELD: A STUDY IN SUSTAINABLE DEVELOPMENT - Al Ibrahimi, Suhaila Najem (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to evaluate the suitability of groundwater for multiple uses, including agricultural irrigation, human consumption, animal drinking, and poultry farming, in selected areas of the East Baghdad oil field (Rashidiya and the southern region of Baghdad), with a focus on sustainable water resource management. Method: Laboratory analyses were conducted based on international water quality standards to assess key physicochemical elements, and Geographic Information System (GIS) techniques were employed to transform raw spatial data into a digital database for mapping and generating hydrological tables. Results: The findings indicate spatial variation in groundwater quality across the study area, with certain zones exhibiting acceptable standards for agricultural and livestock use, while other zones were unsuitable for direct human consumption due to elevated concentrations of specific elements. Novelty: The study provides an integrated approach combining laboratory assessment with GIS-based spatial analysis, offering a practical framework for monitoring, mapping, and managing groundwater resources in oil field regions under environmental stress, thereby contributing to long-term sustainability strategies.